2006
DOI: 10.1364/ol.31.002492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of focal spot size on in-band 135 nm extreme ultraviolet emission from laser-produced Sn plasma

Abstract: The effect of focal spot size on in-band 13.5 nm extreme ultraviolet (EUV) emission from laser-produced Sn plasmas was investigated for an EUV lithography light source. Almost constant in-band conversion efficiency from laser to 13.5 nm EUV light was noted with focal spot sizes from 60 to 500 microm. This effect may be explained by the opacity of Sn plasmas. Optical interferometry showed that the EUV emission must pass through a longer plasma with higher density when the focal spot is large, and strong reabsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The dip in the Nd:YAG spectra near 13.5 nm can be explained by the reabsorption in the plasma. 29 The Nd:YAG LPP emits a broader UTA, especially in the higher wavelength side, due to an enhanced rate of three-body recombination arising from its higher electron density. 16 With a chosen irradiation scheme for the prepulse, additional parameters needed to be investigated to obtain an opti-mum EUV conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The dip in the Nd:YAG spectra near 13.5 nm can be explained by the reabsorption in the plasma. 29 The Nd:YAG LPP emits a broader UTA, especially in the higher wavelength side, due to an enhanced rate of three-body recombination arising from its higher electron density. 16 With a chosen irradiation scheme for the prepulse, additional parameters needed to be investigated to obtain an opti-mum EUV conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…However, at the same time, higher lateral expansion can be expected with smaller spot sizes. 2, 19 With a larger spot size, more EUV light can be generated due to high hydrodynamic coupling efficiency, but a longer plasma scale length results in heavier reabsorption and, hence, less EUV light can escape from the plasma. Hence, the final output of 13.5 nm EUV light with varying laser spot size is determined by the balance of the laser energy loss due to the lateral expansion and the reabsorption of EUV light which leads to constant CE irrespective of the laser spot size used.…”
Section: Resultsmentioning
confidence: 99%
“…16 We recently reported that the spot size has negligible effect on the conversion efficiency ͑CE͒ of in-band radiation ͑13.5 nm with 2% bandwidth͒. 19 The constant CE irrespective of the spot size is attributed to the balance of the laser energy loss due to lateral expansion of the plasma and reabsorption of the EUV light.…”
Section: Introductionmentioning
confidence: 99%
“…The picosecond laser is used as a prepulse. The nanosecond laser is used to generate the EUV plasma to match the optimized conditions for efficient generation of 13.5 nm EUV light, 10 called as the pumping pulse hereafter. The two lasers are synchronized with a pulse delay generator ͑Stanford DG535͒ with a jitter less than 0.5 ns.…”
Section: Experimental Arrangementsmentioning
confidence: 99%